Intracranial Pressure during HighVolume Hemofiltration in Severe Sepsis - A. P. Berdnikov; S. I. Goncharenko; T. S. Musaeva; I. B. Zabolotskikh (Общая реаниматология)
Objective: to define the prognostic value of intracranial pressure (ICP) changes in highvolume hemofiltration (HVHF) in patients with severe sepsis and normal preperfusion ICP.Subjects and methods. A retrospective study was conducted in 50 patients (a total of 134 sessions) with severe sepsis and normal baseline ICP who received ther apy using HVHF for extrarenal indications. Based on ICP changes before and after HVHF, the investigators identified 2 groups: 1) no ICP changes (n=81); 2) elevated ICP (n=53).Conclusion. HVHF is ineffective when the normal preperfusion ICP is increased in patients with severe sepsis who have a concurrence of an arteriovenous carbon dioxide difference of more than 8 mm Hg and a Glasgow coma score of less than 10.